Enigmatic Late Permian cockroaches from Isady, Russia (Blattida: Mutoviidae fam. n.) - Vršanský, Peter; Aristov, Danil (Zootaxa, 2012)
Mutovia intercalaria gen. et sp. n. is described from the Upper Permian sediments of Isady in north-western Russia and placed withina new Palaeozoic cockroach family, Mutoviidae fam. n.. The forewing, with very basal, distinct separation of R1 and RS resemblingthe cockroach hind wing and also the forewing of mantises and eoblattids, and with a sharply convex clavus, is unique. The generalvein scheme is closely analogous to Cretaceous mantises (Baissomantis Gratshev et Zherikhin, 1994), but the two taxa are not directlyrelated. The new species comprises about 3% of all fossil insects and 10% of fossil cockroaches at the site, and thus is one of the dom-inant species at the site. Reorganization of the main veins within the taxon suggests the group was rapidly evolving, perhaps becauseof environmental stress. The high coefficient of variability for total number of veins meeting margin (14.5%) is characteristic fornewly emerging (early Palaeozoic and early Mesozoic) lineages and is much higher than for the same characteristic in advanced Pale-ozoic taxa. In spite of an apparently aerodynamic shape of the wing, it likely was not a good flier, as indicated by the extreme variationof veins in the anterior margin and narrow and plastic hind wing remigium. A sex ratio approaching 2:1 suggests that males were moreactive in flight. The new family represents a direct evidence for appearance of new taxa before the Permotriassic boundary and disability of these taxa to cross that crisis.